2018
DOI: 10.1159/000492646
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Ubiquitin-Mediated Proteolytic Degradation of PML/Rarα Fusion Protein in Matrine-Induced Differentiation Sensitivity Recovery of ATRA-Resistant APL (NB4-LR1) Cells: in Vitro and in Vivo Studies

Abstract: Background/Aims: Although the cure rate of acute promyelocytic leukemia (APL) has exceeded 90%, the relapse/refractory APL that resistant to all-trans retinoic acid (ATRA) or ATO was still serious concern. Matrine (MAT) could improve the differentiation ability of ATRA-resistant APL cells. This study aimed to explore how the APL-specific fusion protein was degraded in ATRA-resistant APL with the application of MAT and ATRA. Methods: ATRA-sensitive (NB4) and ATRA-resistant (NB4-LR1) cell lines were used. Nitrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Our previous study reported that matrine induced apoptosis in leukemia cells [ 16 ]. In this study, matrine induced apoptosis of NKTCL cell line NK92 cells in a dose dependent manner from 3.83 ± 0.78% to 62.9 ± 0.66% after matrine treatment at different concentrations for 48 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study reported that matrine induced apoptosis in leukemia cells [ 16 ]. In this study, matrine induced apoptosis of NKTCL cell line NK92 cells in a dose dependent manner from 3.83 ± 0.78% to 62.9 ± 0.66% after matrine treatment at different concentrations for 48 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo usage of matrine for cancer treatment in mice have been reported in several studies. The dose ranges from 25 to 100 mg/kg (Zhou et al, 2014; Wu et al, 2017; Cho et al, 2018; Shen et al, 2018; Wu et al, 2018). In our study, we use 80 mg/kg (0.32 mmol/kg) and the 7-days daily intraperitoneal administration shows distinct anticancer effect without significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when differentiation was reestablished in maturation-resistant APL cells (by addition of 8-CPT-cAMP to ATRA treatment), autophagy activation and p62/SQSTM1 upregulation were both restored in these cells, underscoring the idea that autophagy and differentiation are interconnected processes. Furthermore, matrine, an alkaloid found in plants from the genus Sophora, was shown to improve the differentiation ability of ATRA-resistant APL cells through induction of autophagy and ubiquitin degradation of PML-RARα [74]. In another study, the addition of lithium (an autophagy inducer) to ATRA reactivated differentiation in ATRA maturation-resistant HL60-Diff-R AML cells, emphasizing the concept that autophagy modulation may represent a means to restore differentiation [12].…”
Section: Regulation Of Autophagy During Differentiation Of Apl Celmentioning
confidence: 99%